A case report of fowl plague keratoconjunctivitis. - Taylor, H R (1977)
A case of human fowl plague keratoconjunctivitis occurred after accidental laboratory exposure. The conjunctivitis was characterised by follicle formation and a mucopurulent discharge, and ran a self-limiting course over two weeks. The keratitis was of an unusual type and consisted of small intraepithelial opacities, which appeared after one week and resolved completely over the next three weeks. The infection, confirmed by viral culture, was produced by Dutch strain (Hav 1 Neq 1) of fowl plague virus.